Effect of Low-Level Laser Irradiation on the Proliferation of Human Chondrocytes: An In Vitro Study: LLLI irradiation effect on the proliferation of human chondrocyte - Anbari, Fahimeh; Khalighi, Hamidreza; Baharvand, Maryam; Khosousi sani, Sahba; Sharaki, Mani; Yadegari, Zahra; Mojahedi Nasab, Seyed Masoud; Khosousi sani, Mohammad (Journal of Lasers in Medical Sciences, 2024)
Introduction: Chondrocytes are the major cells in hyaline cartilage playing a crucial role in maintaining the mechanical resilience of the tissue. We assessed the effect of an 808nm diode laser on the proliferation of human chondrocytes. Methods: This study was conducted on human chondrocytes in vitro. The cells were divided into 5 cases and one control group. The cells were irradiated by low-level laser 808 nm, with energy levels of 1, 2, 3 J/cm² (0.2 W, for 5, 10, and 15 seconds), 4 J/cm² (0.3 W,13 s), and 5 J/ cm² (0.4 W,12 s). The culture was incubated for 24 hours. The MTT assay was performed to determine the cell viability. After 72 hours of incubation, the procedure was reperformed to assess the effect of incubation duration. The cell viability in terms of incubation duration and irradiation parameters were investigated by a two-way ANOVA test. Pairwise comparisons were performed using the Bonferroni test. Results: In the 72-hour incubation group, cell viability in the group that received 5 J/cm² energy was significantly lower than that in the groups receiving 1 J/cm², 2 J/cm², and 4 J/cm² irradiation. The variables of time (P=0.001) and energy level (P=0.024) had significant effects on the cell viability of the samples. In the 24-hour incubation groups, no significant difference in cell viability was observed. Conclusion: The diode 808 nm Low-level laser irradiation (LLLI) at doses of 5 J/cm² and less did not show a significant increase in the proliferation of chondrocytes (regardless of incubation time). However, the best survival rate of chondrocytes was observed in the group of 4 J/cm² with 72-hour incubation.